When do parents and child health professionals agree on child's psychosocial problems? Cross-sectional study on parent–child health professional dyads. Issue 1 (December 2016) - Crone, Mathilde; Zeijl, Elke; Reijneveld, Sijmen
Abstract Background About one third of all parents have concerns about their child's psychosocial development. Agreement between child health professionals (CHPs) and parents about such concerns may improve treatment adherence and outcomes. This study investigates which child, parenting and/or environmental stressors are associated with (dis)agreement in concerns regarding psychosocial problems in children, in parent-CHP dyads. Methods During routine child health assessments, data were collected from a sample of children aged 14 months to 12 years (n = 3, 870). CHPs registered the psychosocial problems that they identified, and parents reported their concerns. Child psychosocial stressors were measured with the ITSEA/CBCL, and the child's history of psychosocial problems. Environmental stressors referred to stressful family/contextual situations in the past year, and parenting stressors to perceived parenting efficacy. Results The CHPs and parents disagreed on 36.4 % of the children. CHPs based their identification of problems mainly on children's history of past problem (OR = 5.85, 95 % CI = 4.74–7.22). Parental concerns were most likely in case of an increased ITSEA/CBCL score (OR = 7.69, CI = 5.39–10.97). CHP-parent agreement was more likely in case of a combination of child psychosocial, parenting and environmental stressors (OR = 35.58, CI = 24.11–52.48). Parental concernsnot confirmed by the CHP were associated with higher educated parents, originating from an industrialized country, and younger children. The CHP-identified problemsnot confirmed by parental concerns were associated with older children. Conclusion Agreement between CHPs and parents is associated with a co-occurrence of child, parenting and environmental stressors. Improved agreement between CHP and parents will increase the likelihood of shared decision-making regarding follow-up care and compliance with advice.